2013
DOI: 10.1242/dev.093229
|View full text |Cite
|
Sign up to set email alerts
|

A replication-dependent passive mechanism modulates DNA demethylation in mouse primordial germ cells

Abstract: SUMMARYGermline cells reprogramme extensive epigenetic modifications to ensure the cellular totipotency of subsequent generations and to prevent the accumulation of epimutations. Notably, primordial germ cells (PGCs) erase genome-wide DNA methylation and H3K9 dimethylation marks in a stepwise manner during migration and gonadal periods. In this study, we profiled DNA and histone methylation on transposable elements during PGC development, and examined the role of DNA replication in DNA demethylation in gonadal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 48 publications
(85 reference statements)
3
58
1
Order By: Relevance
“…Just as epigenetically modified phenotypes are variable across generations, so too is DNA methylation, the extent of which can occur across a continuum. In fact, with each subsequent generation, DNA methylation patterns are created, maintained, cleared (erased) and then re-established during the life cycle and subsequent inheritance of a phenotype (Alvarado et al, 2014a;Alvarado et al, 2014b;Golbabapour et al, 2011;Ohno et al, 2013). Thus, patterns of decline in DNA methylation or other epigenetic molecular agent could be the causal agent behind a decline in the epigenetically modified phenotype, until the effect had either disappeared or fallen below a threshold for detection of the modified phenotype.…”
Section: Reviewmentioning
confidence: 99%
“…Just as epigenetically modified phenotypes are variable across generations, so too is DNA methylation, the extent of which can occur across a continuum. In fact, with each subsequent generation, DNA methylation patterns are created, maintained, cleared (erased) and then re-established during the life cycle and subsequent inheritance of a phenotype (Alvarado et al, 2014a;Alvarado et al, 2014b;Golbabapour et al, 2011;Ohno et al, 2013). Thus, patterns of decline in DNA methylation or other epigenetic molecular agent could be the causal agent behind a decline in the epigenetically modified phenotype, until the effect had either disappeared or fallen below a threshold for detection of the modified phenotype.…”
Section: Reviewmentioning
confidence: 99%
“…Protein complexes were washed with wash buffer (20 mM HEPES, pH 7.6, 1.5 mM MgCl 2 , 150 mM NaCl, 0.2 mM EDTA, 0.5 mM DTT and 20% glycerol) and eluted by boiling with SDS sample buffer. ChIP analyses were performed as previously described (Ohno et al, 2013).…”
Section: Western Blotting Immunoprecipitation Analyses and Chip Analmentioning
confidence: 99%
“…Recent whole-genome bisulphite sequencing has shown that global loss of DNA methylation occurs in migrating PGCs, whereas some resistant regions become demethylated only in gonadal PGCs (Seisenberger et al, 2012). Active repression of Dnmt3a, Dnmt3b and Uhrf1, coupled with rapid proliferation of PGCs, might trigger replication-dependent passive demethylation in developing PGCs (Kagiwada et al, 2013;Ohno et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The epigenetic programme induced primarily by BLIMP1 and PRDM14 leads to global DNA demethylation towards an epigenetic ground state in early PGCs Hajkova et al, 2008;Hajkova et al, 2010;Ohno et al, 2013;Seisenberger et al, 2012) (Fig. 4).…”
Section: The Genetic Network For Pgc Specification Initiates the Epigmentioning
confidence: 99%
“…For example, the repression of Uhrf1 (Bostick et al, 2007) and Dnmt3b by BLIMP1 and PRDM14 promotes DNA replication-coupled DNA demethylation in PGCs. Additionally, TET1 and TET2, which are bound by PRDM14, catalyse hydroxylation of 5-methyl-cytosine, which provides an additional parallel redundant mechanism for DNA demethylation in PGCs Ma et al, 2011;Ohno et al, 2013;Seisenberger et al, 2012). There is potentially a role for a base excision repair mechanism (Hajkova et al, 2008) that could contribute to the erasure of imprints.…”
Section: The Genetic Network For Pgc Specification Initiates the Epigmentioning
confidence: 99%